2015
DOI: 10.1159/000430199
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Effect of Liraglutide is Mediated by Glucagon-Like Peptide 1 Receptor-Mediated Activation of cAMP/PKA/CREB Pathway

Abstract: Background/Aims: Glucagon-like peptide-1 (GLP-1)-based drugs are being used to achieve better glucose control in patients with type 2 diabetes, and GLP-1 mimetics such as liraglutide have shown therapeutic potential in preventing diabetes-related microvascular and macrovascular complications as well as comorbidities such as neurodegenerative disorders. In the present study, we investigated the effects of liraglutide on primary rat cortical astrocytes treated with advanced glycation end-products (AGEs). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…Astroglial up-regulation of GLP-1 receptors may be an important mechanism of action for GLP-1 agonism in the brain as GLP-1 receptors are up-regulated in reactive astroglia after cortical lesion (Chowen et al, 1999) and protect astrocytes in culture (Bao et al, 2015). Furthermore, reactive astroglia express neuroglobin in murine EAE (DellaValle et al, 2010), a neuroprotective protein that is up-regulated by liraglutide treatment (DellaValle et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Astroglial up-regulation of GLP-1 receptors may be an important mechanism of action for GLP-1 agonism in the brain as GLP-1 receptors are up-regulated in reactive astroglia after cortical lesion (Chowen et al, 1999) and protect astrocytes in culture (Bao et al, 2015). Furthermore, reactive astroglia express neuroglobin in murine EAE (DellaValle et al, 2010), a neuroprotective protein that is up-regulated by liraglutide treatment (DellaValle et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that GLP-1R played an anti-apoptosis role in INS-1 cells [23], H9c2 cells [24] and astrocytes [15]. GLP-1 binding to GLP-1R resulted in body weight loss due to decreased food intake.…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 can decrease hyperglycemia, improve beta cell growth, reduce food intake and body weight [14], and has anti-ERS effects [15]. A clinical study reported that patients with type 2 diabetes have significantly lower levels of the predominant circulating saturated free fatty acid following a GLP-1 subcutaneous infusion, with 2 kg of weight loss [16].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that nimodipine protected the brain from CBH by activating the Akt/CREB signaling pathway, suggesting that CREB plays an important role in CBH-related conditions [46]. Studies have also shown that liraglutide exerts its neuroprotective effects via activation of the cAMP/PKA/CREB pathway [47]. CREB was previously reported to contribute to the regulation of BACE1 [48].…”
Section: Discussionmentioning
confidence: 99%